Holistic approach to management of acne: Exploring the evidence - Sujata R Mehta Ambalal (Wolters Kluwer Medknow Publications, 2023)
A shift in the understanding of acne from a skin disease to a systemic, chronic inflammatory, lifestyle disease has fueled our curiosity about holistic ways to manage it. As with other noncommunicable diseases, long-term management needs a comprehensive approach. Apart from topical and systemic medications, changes in diet and lifestyle can help us achieve superior and long-lasting results. Moreover, as the biochemical pathways linking risk factors to acne are getting clearer, the potential prospect of early holistic management of acne preventing or delaying other lifestyle disorders such as obesity, diabetes, or cardiovascular disease is encouraging.